Pengembangan inventori kecanduan internet untuk siswa sekolah menengah atas - Nadzifah, Laila Ummi; Bariyyah, Khairul; Permatasari, Devi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2020)
This study aims to develop an inventory suitable for counselors to use to measure students' internet addiction. This research method is a development research. The number of samples was 302 students at senior high school Malang City who were selected by using the Random Sampling technique. The inventory was compiled using the Internet addiction Likert scale and the validator test score sheet. Data analysis using Pearson Product Moment to calculate the validity of the item, Alpha Cronbach to calculate the reliability coefficient and factor analysis to determine the adequacy of the sample or the feasibility of all inventory statement items. The results of this development research resulted in an internet addiction inventory consisting of 43 valid statement items and had a high reliability coefficient of 0.933. This internet addiction inventory has 6 correlated factors, according to the internet addiction construct based on Young's theory which underlies the development of inventory. This inventory is needed by counselors to measure internet addiction in students.